Migration and Remittances : Recent Developments and Outlook - Ratha, Dilip K.; De, Supriyo; Dervisevic, Ervin; Plaza, Sonia; Schuettler, Kirsten; Shaw, William; Wyss, Hanspeter; Yi, Soonhwa; Yousefi, Seyed Reza (2016)
Using newly available census data, the stock of international migrants is estimated at 247 million in 2013, significantly larger than the previous estimate of 232 million, and is expected to surpass 250 million in 2015. Migrants’ remittances to developing countries are estimated to have reached $436 billion in 2014, a 4.4 percent increase over the 2013 level. All developing regions recorded positive growth except Europe and Central Asia (ECA), where remittance flows contracted due to the deterioration of the Russian economy and the depreciation of the ruble. In 2015, however, the growth of remittance flows to developing countries is expected to moderate sharply to 0.9 percent to $440 billion, led by a 12.7 percent decline in ECA and slowdown in East Asia and the Pacific, Middle-East and North Africa, and Sub-Saharan Africa. The positive impact on flows of a robust recovery in the US will be partially offset by continued weakness in Europe, the impact of lower oil prices on the Russian economy, the strengthening of the US dollar, and tighter immigration controls in many source countries for remittances. Remittance flows are expected to recover in 2016 to reach $479 billion by 2017, in line with the more positive global economic outlook.